2017
DOI: 10.3151/jact.15.165
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alkalis on Cementitious Materials:Understanding the Relationship between Composition, Structure, and Volume Change Mechanism

Abstract: Journal of Advanced AbstractPrevious studies demonstrated that alkalis can considerably affect the volumetric properties of hardened cementitious binders, including shrinkage, creep, and micro-cracking. The objective of this paper is to reexamine the effect of alkalis on the composition, nanostructure, phase stability, and morphology of calcium-silicate-hydrate (C-S-H) in cementitious materials, and to further propose a conceptual model bridging the C-S-H characters with its volume change mechanisms in alkali-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 49 publications
1
6
0
Order By: Relevance
“…The large scatter is mainly due to the development of microcracks, which were observed visually and microscopically. Microcracks were present at both surfaces of the sample (Figure 16), but also inside the sample, as also observed by Collins and Sanjayan [74], Ye et al [75], Thomas et al [71], and Hubler et al [76]. Nevertheless, microcracks did not influence the compressive strength.…”
Section: Resultssupporting
confidence: 76%
“…The large scatter is mainly due to the development of microcracks, which were observed visually and microscopically. Microcracks were present at both surfaces of the sample (Figure 16), but also inside the sample, as also observed by Collins and Sanjayan [74], Ye et al [75], Thomas et al [71], and Hubler et al [76]. Nevertheless, microcracks did not influence the compressive strength.…”
Section: Resultssupporting
confidence: 76%
“…Moreover, the incorporation of sulfate salts, regardless of the conjugated cation type, noticeably shortens the setting time of LC 3 pastes. The acceleration role of alkalis on earlyage hydration of cementitious systems is also reported in pure OPC systems [12,31,32].…”
Section: Setting Timesmentioning
confidence: 60%
“…Many previous studies have documented that alkalis have dramatic effects on the hydration kinetics and microstructural development, as well as mechanical and durability performance of hardened OPC materials [12,13]. For instance, it was reported that the alkali salt contamination in OPC accelerates carbonation, deepening the carbonation depth, and shortening the initiation time of carbonation-induced steel corrosion [14].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a much higher amount of aphthitalite precipitated at 60 • C compared to at 40 • C, indicating that with increasing temperature above ambient, the formation of aphthitalite is increased due to a higher release of alkalis from the clinker phases. Apart from alkali sulfates present in the clinkers, the alkalis, which are incorporated in the main clinker phases, mainly in calcium sulfoaluminate [37], could be released through the dissolution of these phases [37,59] as well, reacting with sulfate from the gypsum, and form the alkali sulfate phase aphthitalite. Namely, another alkali sulfate phase thenardite (Na 2 SO 4 ) was found forming in calcium sulfoaluminate cements at high alkalinity, explained as a product of excess alkalis initially reacting with anhydrite, which retards calcium sulfoaluminate hydration and ettringite formation [60].…”
Section: Discussionmentioning
confidence: 99%